Catalogue of Irish manuscripts in Houghton Library, Harvard University - Buttimer, Cornelius G. (University of Notre Dame Press, 2022)
The first full account of North America's largest collection of traditional Irish-language manuscripts. Harvard University has the largest collection of Irish-language codices in North America, held in Houghton Library, its rare book repository. The manuscripts are a part of the age-old heritage of Irish book production, dating to the early Middle Ages. Handwritten works in Houghton contain versions of medieval poetry and sagas, recopied in the eighteenth and nineteenth centuries, to which period most of the library's documents belong. Contemporary writings from that time, as well as ones by the post-Famine Irish immigrant community in the United States, are included. This catalogue describes the collection in full for the first time and will be an invaluable aid to research on Irish and Irish American cultural and literary output. The author's introduction examines how the collection was formed. This untold story is an important chapter in America's intellectual history, reflecting a phase of unprecedented expansion in Harvard University's scholarship and teaching during the early twentieth century when the institution's program of studies began to accommodate an increasing range of European languages and literatures and their sources. This indispensable guide to a major repository's records of the Irish past, and of America's Irish diaspora, will interest specialists in early and post-medieval codices. It should prove of relevance as well to scholars and students of comparative literature, cultural studies, and Irish and Irish American history.